Unlocking the Power of ChatGPT: Students’ Interest in Asian Parliamentary Debate Classroom - Syaripuddin, Rahmatullah; Rasyid, Asriadi; Darwis, Aswinda; Suhria, Suhria; Hasanuddin, Nurqadriyanti (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
This study aims to measure students’ interest in using ChatGPT to teach English using the debate clinic method to improve students’ speaking skills. Descriptive quantitative research involving 14 students of the Islamic Religious Education Study Program, STAI DDI Pinrang, used a questionnaire to measure four indicators of learning interest: feelings of pleasure, interest, paying attention, and involvement. The results revealed that the student’s average score of learning interest reached 77, indicating a relatively high interest. Students’ participation in formulating and refuting arguments during debates proves that ChatGPT positively impacts the development of students’ critical thinking skills. Therefore, this study contributes to developing technology-based pedagogy, especially in academic debate. Integrating ChatGPT in the debate process allows teachers to create a more dynamic and interactive learning environment where students can be more actively involved. However, the study has several limitations. First, the limited number of samples, so generalizing the study results may not apply to a broader population. Additionally, it only focused on one study program at one institution, so the results may not reflect the situation at other institutions. Therefore, further research can explore other factors that influence learning interest, such as pedagogical aspects and technology used in the learning process.